MARTIN HEIDEGGER'S THE QUESTION ABOUT TECHNIC - A TRANSLATION AND COMMENTARY - Alexander, Edwin M. (My University, 1973)
It might be asked as to whether or not the translator has a muse. The question must seem at first to be an impossibility: the translator is only a technician, a correlator of existing thoughts and words, or even worse:
Such is our pride, our folly and our fate, That only those who cannot write, translate.
Yet in an undertaking such as the one at hand, the translation of the words of a man which are so profoundly difficult in his own language, one must have a trust in even the impossible.
Muse or no muse, I hereby renounce full credit for the translation which follows and acknowledge my great debt to the students of Religion 775 of 1970 and 1972 whose questionings were responsible for innumerable revisions both of particular passages and words and of the general tone and understanding of the entire lecture 0 And of course to George Grant, who conceived of this translation, inspired it, and without whose 'invaluable - understandings and criticisms this undertaking would have been but half what it is at present.
Keywords: Religion; Religion